Impact of the strategy, strategy-making and its formalization in the export performance of SMEs, in the province of Cartago - Navarro-Calvo, Mónica M. (2016)
This research analyzed the impact of the strategy, the strategy-making and its formalization on the export performance of SMEs, located in the province of Cartago (Costa Rica) that exported in 2013. To collect the information the study used a database of the index export performance (IDE) from PROCOMER and a structured questionnaire, to evaluate the strategic area of the company, which was sent via email to 35 companies and self-administered by them. From the information gather, it found that the owners and managers strategic knowledge is basic, also that companies do not handle a defined strategy, but a hybrid of these. Furthermore, hypothesis tests were conducted using bivariate correlations to determine the existence of a relationship between the IDE and evaluated different aspects, this was rejected since there was no significant relationship in any of the cases. Finally, it can be concluded that the strategic aspects evaluated are not important on terms of export performance is concerned.